Variations of microbiota and metabolites in rhizosphere soil of Carmona microphylla at the co-contaminated site with polycyclic aromatic hydrocarbons and heavy metals - Ying Zhang; Fanghan Qian; Yanyu Bao (Ecotoxicology and Environmental Safety)
Co-contamination with organic/inorganic compounds is common in industrial area and poses a great risk to local soil ecological environment. In this study, an operating ink factory site co-contaminated with polycyclic aromatic hydrocarbons (PAHs, mild to moderate pollution level) and heavy metals (HMs, heavy pollution level) was selected and screened for native vegetation, Carmona microphylla. High-throughput sequencing and metabolomics were mainly used to investigate the responses of soil bacteria and metabolites to the composite pollution and rhizosphere effect. As the results showed, among three pollution levels, a medium level of pollution was favorable to increase the richness and diversity of soil bacterial community, while high level of pollution greatly decreased special OTUs number. In addition, HMs were the most significant factors driving bacterial community structure, especially for Cd. The influence of medium molecular weight PAHs with 4 rings (MMW-PAHs) on dominant bacteria was greater than low molecular weight PAHs with 2–3 rings (LMW-PAHs) and high molecular weight PAHs with 5–6 rings (HMW-PAHs). Soil bacterial function was affected mainly by pollution level, but not rhizosphere effect, in which high pollution level changed α diversity and structure and composition of C- and N-cycling bacteria. Rhizosphere promoted network complexity by increasing the connection densities among bacterial communities, metabolites, soil properties and the involved number of metabolites. Compared to HMs, PAHs played a more important role in shaping bacterial community through affecting metabolites in non-rhizosphere soil, which was different from rhizosphere soil with a more significant effect of HMs than PAHs. Some key bacterial taxa have established resistance to HMs in rhizosphere soils, whereas they were sensitive to compound contamination in non-rhizosphere soils. Some key bacterial taxa are resistant to HMs in rhizosphere soils, whereas they are susceptible to complex contamination in non-rhizosphere soils, which could be a consequence of the rhizosphere by regulating soil metabolism. It also provides a valuable reference for how co-contaminants and rhizosphere effect shape together soil bacterial community through the changes of soil metabolites.